Bioactivity of commercial botanical insecticides against Duponchelia fovealis (Lepidoptera: Crambidae) - Moraes, Bruno Roberto de (2025)
Botanical insecticides have emerged as valuable tools for integrated pest management, offering particularly appealing ecological advantages in strawberry cultivation. Restrictions in the phytosanitary schedule pose challenges, such as controlling Duponchelia fovealis Zeller (Lepidoptera: Crambidae), a significant pest for this crop. This study aimed to evaluate the toxicity and lethal concentrations of two commercial botanical insecticides, one based on Sophora flavescens extract and the other on Azadirachta indica oil, against D. fovealis under laboratory conditions. Seven concentrations were tested for each botanical insecticide: S. flavescens extract (oxymatrine; Matrine®) at 6%, 4%, 2%, 1.5%, 1%, 0.75%, and 0.5%; and A. indica (azadirachtin; Fitoneem®) at 8%, 6%, 4%, 1.5%, 1%, 0.75%, and 0.5%). The synthetic insecticide chlorfenapyr (Pirate®) was used as a positive control (0.0104%, 0.0139%, 0.0186%, 0.0440%, 0.0587%, 0.0789%, and 0.1042%), while distilled water was used as a negative control. Topical applications were performed on third-instar larvae of D. fovealis to determine lethal concentrations through bioassays. The S. flavescens-based botanical insecticide exhibited the highest toxicity against D. fovealis, resulting in a mortality rate of 95.9% at a 6% concentration. A. indica at a 6% concentration resulted in a maximum mortality of 66.3%. The lethal concentrations (LC50 and LC90) observed were 1.97% and 5.84% for S. flavescens and 3.93% and 30.57% for A. indica, respectively. Therefore, the botanical insecticide based on S. flavescens extract shows high potential as an alternative for controlling D. fovealis, a significant pest in strawberry cultivation.